In vivo short-term exposure to residual oil fly ash impairs pulmonary innate immune response against environmental mycobacterium infection - Delfosse, Veronica Cecilia; Tasat, Deborah Ruth; Gioffre, Andrea (Wiley, 2019)
Epidemiological studies have shown that pollution derived from industrial and vehicular transportation induces adverse health effects causing broad ambient respiratory diseases. Therefore, air pollution should be taken into account when microbial diseases are evaluated. Environmental mycobacteria (EM) are opportunist pathogens that can affect a variety of immune compromised patients, which impacts significantly on human morbidity and mortality. The aim of this study was to evaluate the effect of residual oil fly ash (ROFA) pre-exposure on the pulmonary response after challenge with opportunistic mycobacteria by means of an acute short-term in vivo experimental animal model. We exposed BALB/c mice to ROFA and observed a significant reduction on bacterial clearance at 24 h post infection. To study the basis of this impaired response four groups of animals were instilled with (a) saline solution (Control), (b) ROFA (1 mg kg21 BW), (c) ROFA and EM-infected (Mycobacterium phlei, 8 3 106 CFU), and (d) EMinfected. Animals were sacrificed 24 h postinfection and biomarkers of lung injury and proinflammatory madiators were examined in the bronchoalveolar lavage. Our results indicate that ROFA was able to produce an acute pulmonary injury characterized by an increase in bronchoalveolar polymorphonuclear (PMN) cells influx and a rise in O2 2 generation. Exposure to ROFA before M. phlei infection reduced total cell number and caused a significant decline in PMN cells recruitment (p<0.05), O2 2 generation, TNFa (p<0.001), and IL-6 (p<0.001) levels. Hence, our results suggest that, in this animal model, the acute short-term pre-exposure to ROFA reduces early lung response to EM infection